The Guernsey Literary and Potato Peel Pie Society - Shaffer, Mary Ann.; Barrows, Annie (New York, N.Y. : Dial Press, 2008)
After World War II, a journalist travels to the island of Guernsey to meet residents who resisted the Nazi occupation.
Map on lining papers.
Keywords: Women authors -- Fiction; Book clubs (Discussion groups) -- Fiction; London (England) -- History -- 20th century -- Fiction; England -- Fiction; Epistolary fiction